2022
DOI: 10.1097/mao.0000000000003766
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Sociodemographic Data in Cochlear Implant Clinical Trials: A Systematic Review

Abstract: Objective: The purpose of this study was to systematically evaluate the literature on the frequency of reporting of sociodemographic data (gender, race, ethnicity, education status, health insurance status, geographic location of residence, and socioeconomic status) among interventional clinical trials involving cochlear implant patients. Databases Reviewed: A systematic search was performed in PubMed, Cochrane Database of Systematic Reviews, Web of Science, and SCOPUS to identify peer reviewed research. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…52 It is unknown if or how this translates to skin pigmentation. These racial and ethnic ARHL prevalence estimates may not be accurate due to longstanding inequitable access to hearing care, 43 underreporting of sociodemographic data of participants in hearing research, 53 and underrepresentation in hearing-related clinical trials 54 among some populations.…”
Section: Health Care Burden Epidemiologymentioning
confidence: 99%
“…52 It is unknown if or how this translates to skin pigmentation. These racial and ethnic ARHL prevalence estimates may not be accurate due to longstanding inequitable access to hearing care, 43 underreporting of sociodemographic data of participants in hearing research, 53 and underrepresentation in hearing-related clinical trials 54 among some populations.…”
Section: Health Care Burden Epidemiologymentioning
confidence: 99%
“…3 For hearing health care research, sociodemographic data have rarely been collected and reported; when these data have been reported, the samples are often not representative of the patient population. 4,5 Successful recruitment and retention of a study sample that is representative of the patient population begins at the research protocol design phase. 6 Recruitment strategies to target historically underrepresented patient populations vary in degree of success by location, intervention type, and study design.…”
Section: Introductionmentioning
confidence: 99%